Demokrasi Indonesia dan Citanegara Integralistik - Tambunan, Arifin S.S (Unisia, 2016)
The life ofa state is a continuos process of integration, There must be a dynamic stugle to make an integrated state happen. This article tehoritically illustrates the idea of Soepomo concerning the Integralistic State and criticizes some approaches opposing to it. Different from other writings, this article combines legal ang political approaches.